Sequential reduction of high hydride count octahedral rhodium clusters [Rh6(PR3)6H12][BArF4]2: redox-switchable hydrogen storage. - Brayshaw, S; Harrison, A; McIndoe, J; Marken, F; Raithby, P; Warren, J; Weller, A (2007)
Cyclic voltammetry on the octahedral rhodium clusters with 12 bridging hydride ligands, [Rh6(PR3)6H12][BArF4]2 (R = Cy Cy-[H12]2+, R = iPr iPr-[H12]2+; [BArF4]- = [B{C6H3(CF3)2}4]-) reveals four potentially accessible redox states: [Rh6(PR3)6H12]0/1+/2+/3+. Chemical oxidation did not produce stable species, but reduction of Cy-[H12]2+ using Cr(eta6-C6H6)2 resulted in the isolation of Cy-[H12]+. X-ray crystallography and electrospray mass spectrometry (ESI-MS) show this to be a monocation, while EPR and NMR measurements confirm that it is a monoradical, S = 1/2, species. Consideration of the electron population of the frontier molecular orbitals is fully consistent with this assignment. A further reduction is mediated by Co(eta5-C5H5)2. In this case the cleanest reduction was observed with the tri-isopropyl phosphine cluster, to afford neutral iPr-[H12]. X-ray crystallography confirms this to be neutral, while NMR and magnetic measurements (SQUID) indicate an S =1 paramagnetic ground state. The clusters Cy-[H12]+ and iPr-[H12] both take up H2 to afford Cy-[H14]+ and iPr-[H14], respectively, which have been characterized by ESI-MS, NMR spectroscopy, and UV-vis spectroscopy. Inspection of the frontier molecular orbitals of S = 1 iPr-[H12] suggest that addition of H2 should form a diamagnetic species, and this is the case. The possibility of "spin blocking" in this H2 uptake is also discussed. Electrochemical investigations on the previously reported Cy-[H16]2+ [J. Am. Chem. Soc. 2006, 128, 6247] show an irreversible loss of H2 on reduction, presumably from an unstable Cy-[H16]+ species. This then forms Cy-[H12]2+ on oxidation which can be recharged with H2 to form Cy-[H16]2+. We show that this loss of H2 is kinetically fast (on the millisecond time scale). Loss of H2 upon reduction has also been followed using chemical reductants and ESI-MS. This facile, reusable gain and loss of 2 equiv of H2 using a simple one-electron redox switch represents a new method of hydrogen storage. Although the overall storage capacity is very low (0.1%) the attractive conditions of room temperature and pressure, actuation by the addition of a single electron, and rapid desorption kinetics make this process of interest for future H2 storage applications.